Center-Pivot-Irrigated Sunflowers—Oil Type - O'Brien, Daniel M.; Sartwelle III, James D. (My University, 1995)
The cost-return projection estimates the cost of producing center-pivot-irrigated sunflowers in Kansas.
MF800_1995_10
Keywords: MF800; Economics; Crops; MF